Preparation, characterization and morphology of chitosan film containing nifedipine - Chinh, Nguyen Thuy; Thu Trang, Nguyen Thi; Mai, Tran Thi; Hoang, Thai (Vietnam Journal of Science and Technology, 2015)
This paper presents some characters and morphology of compound of chitosan (CS) and nifedipine (NIF) with various NIF content prepared by solution method. The characteristic peaks of some groups in CS and NIF in Fourier transform infrared spectroscopy (FTIR) spectra of the CS/NIF compound shift slightly in comparison with that in the FTIR spectra of CS and NIF. This proved that CS and NIF were interacted with each other. NIF dispersed in the CS matrix with the relatively small size from 200 nm to 2 µm. Thermal analysis results showed that the CS/NIF compound has less thermostable than the CS. The calibration equations of NIF were set up from data of UV-Vis spectra and regression coefficients obtained higher than 0.996. In vitro release study of CS/NIF compounds indicated drug release rate was almost higher in pH 7.4 solution than that in pH 6.8 solution for the samples containing 10, 30 and 50 wt.% NIF.